Observations of Interactions between Puma, Puma concolor, and Introduced European Red Deer, Cervus elaphus, in Patagonia - Fluck, Werner Thomas (2004)
Direct observations of interactions between native Puma (Puma concolor) and introduced European Red Deer (Cervus elaphus) in Patagonia are discussed with respect to the absence of evolutionary sympatry. Although the founding stock of European Red Deer had been lacking natural predation pressure for considerable time due to the previous extinction of large predators, these observations suggested that inherent antipredator behavior of European Red Deer toward this novel predator, once detected, was effective and may partially explain the success of European Red Deer as an invasive species. Puma behavior supported the view that they are a generalist predator which opportunistically utilizes new prey species like European Red Deer.